Development Of A Library Navigation System Using Dijkstra’s Algorithm - A. A. M. Salleh; K. Abdulrahim (Penerbit Universiti Teknikal Malaysia Melaka, 2024)
Journal of Engineering and Technology (JET) Volume: 14 No: 2 (page: 189-200)